Job Quality Gaps between Migrant and Native Gig Workers: Evidence from Poland - Zuzanna Kowalik; Piotr Lewandowski; Pawel Kaczmarczyk (Institute of Labor Economics (IZA), 2023)
The gig economy has grown worldwide, opening labour markets but raising concerns about precariousness. Using a tailored, quantitative survey in Poland, we study taxi and delivery platform drivers' working conditions and job quality. We focus on the gaps between natives and migrants, who constitute about a third of gig workers. Migrants take up gig jobs due to a lack of income or other job opportunities much more often than natives, who mostly do it for autonomy. Migrants' job quality is noticeably lower regarding contractual terms of employment, working hours, work-life balance, multidimensional deprivation, and job satisfaction. Migrants who started a gig job immediately after arriving in Poland are particularly deprived. They also cluster on taxi platforms which offer inferior working conditions. Poland is a New Immigration Destination where ethnic economy is poorly developed, institutions to support migrants are weak and access to migrant networks is limited to several nationalities only. The gig economy can be an arrival infrastructure, but its poor working conditions may exacerbate the labour market vulnerabilities of migrants and hinder mobility to better jobs.
Keywords: J28; J61; J21; 330; gig jobs; platform economy; job quality; immigrant workers